The labor supply and retirement behavior of China's older workers and elderly in comparative perspective - John Giles; Dewen Wang; Wei Cai (Institute for the Study of Labor (IZA), 2011)
This paper highlights the employment patterns of China's over 45 population and, for perspective, places them in the context of work and retirement patterns in Indonesia, Korea, the United States, and the United Kingdom. As is common in many developing countries, China can be characterized as having two retirement systems: a formal system, under which urban employees receive generous pensions and face mandatory retirement by age 60, and an informal system, under which rural residents and individuals in the informal sector rely on family support in old age and have much longer working lives. Gender differences in age of exit from work are shown to be much greater in urban China than in rural areas, and also greater than observed in Korea and Indonesia. Descriptive evidence is presented suggesting that pension eligible workers are far more likely to cease productive activity at a relatively young age. A strong relationship between health status and labor supply in rural areas is observed, indicating the potential role that improvements in access to health care may play in extending working lives and also providing some basis for a common perception that older rural residents tend to work as long as they are physically capable. The paper concludes with a discussion of measures that may facilitate longer working lives as China s population ages.
urn:nbn:de:101:1-201111213156
Keywords: J26; J14; O15; O17; O57; 330; retirement; population aging; labor supply; pensions; China; Indonesia; Korea; Ältere Arbeitskräfte; Arbeitsangebot; Altersgrenze; China; Indonesien; Südkorea; USA; Großbritannien